2020
DOI: 10.1021/acs.jnatprod.0c00892
|View full text |Cite
|
Sign up to set email alerts
|

Linearolactone and Kaempferol Disrupt the Actin Cytoskeleton in Entamoeba histolytica: Inhibition of Amoebic Liver Abscess Development

Abstract: Linearolactone (1) and kaempferol (2) have amebicidal activity in in vitro studies. The type of cell death induced by 1 and 2 and their effects on the virulence of E. histolytica were analyzed by transmission and confocal electron microscopy, reactive oxygen species (ROS) production, and apoptosis, detected by flow cytometry with dichlorofluorescein 2′,7′-diacetate and annexin-V binding, respectively, and confirmed by TUNEL. The interaction of 1 and 2 with actin was analyzed by docking, and the in vivo amoebic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Together with the increase in ROS production, annexin V binding, and DNA fragmentation assays, a possible mechanism of apoptosis-like cell death is suggested. The LL treatment was also able to disarrange the actin cytoskeleton of E. histolytica , which was corroborated by a docking analysis showing that it binds to the allosteric site of actin [ 87 ]. This finding should be further explored in the next steps of research, since actin cytoskeleton signaling pathways are essential for E. histolytica host tissue invasion and therefore represent an attractive target against amebiasis.…”
Section: Mechanisms Of Action Of Essential Oils and Terpenic Compound...mentioning
confidence: 85%
See 1 more Smart Citation
“…Together with the increase in ROS production, annexin V binding, and DNA fragmentation assays, a possible mechanism of apoptosis-like cell death is suggested. The LL treatment was also able to disarrange the actin cytoskeleton of E. histolytica , which was corroborated by a docking analysis showing that it binds to the allosteric site of actin [ 87 ]. This finding should be further explored in the next steps of research, since actin cytoskeleton signaling pathways are essential for E. histolytica host tissue invasion and therefore represent an attractive target against amebiasis.…”
Section: Mechanisms Of Action Of Essential Oils and Terpenic Compound...mentioning
confidence: 85%
“…The LL diterpene was able to induce an apoptosis-like effect with the intracellular production of reactive oxygen species (ROS). Moreover, the compound altered the actin cytoskeleton and reduced the development of amoebic liver abscesses (ALA) in the in vivo experiments [ 87 ].…”
Section: Essential Oils and Terpenic Compounds Against Amitochondriat...mentioning
confidence: 99%
“…LL is a diterpene that was first isolated from Salvia lineata [ 23 ] and later from S. polystachya [ 11 ]. Previous studies have strongly evidenced its antiprotozoal properties, including giardicidal activities [ 24 ]. So far, there are no reports describing its giardicidal mechanism of action; hence, the present work provides evidence that LL exerts cytotoxic damage at the cellular and molecular level in G. intestinalis .…”
Section: Discussionmentioning
confidence: 99%
“…Several drug treatments have indirectly targeted actin, such as Adenophyllum aurantium extract, linearolactone, and kaempferol, which affects the structuration of the actin cytoskeleton [99,100]. However, until now, no immune response study has been reported regarding its interaction with E. histolytica actin.…”
Section: Actinmentioning
confidence: 99%